Launching of an interactive compact disc (CD) featuring a full course material for RELS3 - De La Salle University, Manila (Animo Repository, 2001)
DLSU-Manila Religious Studies Department (RSD) officially launched an interactive compact disc (CD) featuring a full course material for RELS3 during Buwan ng Wika . The CD titled Pilipinong Kristiyanong Moralidad . The CD seek to complement online instruction in the Integrated Virtual Learning Environment (IVLE) website.